2017
DOI: 10.21511/ppm.15(3-2).2017.04
|View full text |Cite
|
Sign up to set email alerts
|

The perceived benefits and barriers to the application of mobile and social networking technologies in Higher Learning Institutions

Abstract: This research investigated on the perceived benefits and barriers to the application of mobile and social networking technologies in South African Higher Learning Institutions (HLIs). A quantitative orientation was used in carrying out the study through self-administered questionnaires and a descriptive quantitative method of analysis was applied. The research population consisted of some students and lecturers from University of Venda (Univen) and University of Limpopo (UL). The research results showed that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Given the extreme popularity of TikTok among Generation Z, and their international accessibility via the medium of the Internet, these short-videos in English language have neither been explored in greater depth in the English language communication education research nor utilized in a wider academic settings by English experts as well as English educators or English language teachers [10]. And so far, research regarding the application of TikTok in the pandemic of Covid-19 are dominated by researchers in the field of Health Communication [21].There has been very little research investigating the use of short social media videos for English language learning by EFL young learners [9]. Dai and Chen [10] argues that English language educators as well as English teachers have neglected the potential benefits of using TikTok for English education purpose by college students for these cohorts of young people spending a lot of time being exposed to TikTok social media community.…”
Section: Issues With Tiktok In English Language Learning and English Language Communication Education For Efl Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the extreme popularity of TikTok among Generation Z, and their international accessibility via the medium of the Internet, these short-videos in English language have neither been explored in greater depth in the English language communication education research nor utilized in a wider academic settings by English experts as well as English educators or English language teachers [10]. And so far, research regarding the application of TikTok in the pandemic of Covid-19 are dominated by researchers in the field of Health Communication [21].There has been very little research investigating the use of short social media videos for English language learning by EFL young learners [9]. Dai and Chen [10] argues that English language educators as well as English teachers have neglected the potential benefits of using TikTok for English education purpose by college students for these cohorts of young people spending a lot of time being exposed to TikTok social media community.…”
Section: Issues With Tiktok In English Language Learning and English Language Communication Education For Efl Studentsmentioning
confidence: 99%
“…Furthermore, [7] stated that there are some potential risks regarding to privacy issues of using social-media for academic purpose among students. It might be unsafe for sharing short-videos in English language by EFL students in public social media space for the purpose of getting comments from their peers or English language experts [3].Posting short self-made short videos in social network communities might cause potential risk for getting attentions from some potential criminals [9].There needs to be more and more effective measures and monitoring mechanism as well as powerful law to be made to protect young internet citizens [9].In conclusion, the application of TikTok in English language education and English language communication competence acquisition is calling for more and more stakeholders to make contributions to establish a wider and more systematic virtual learning system via institutional recognition as well as incorporation along with numerous produced commodities.…”
Section: Issues With Tiktok In English Language Learning and English Language Communication Education For Efl Studentsmentioning
confidence: 99%
“…Recent research has shown that TikTok helps to provide a platform for knowledge sharing and also to promote an innovative learning that improves the motivation and interest of young people (Chakuzira & Kadyamatimba, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also challenges. Successful implementation of this convergence requires investment in technology, teacher training, and careful curriculum planning (Chakuzira & Kadyamatimba, 2017). In addition, concerns about data privacy and the digital divide need to be addressed to ensure that all students can benefit.…”
Section: The Convergence Between Emerging Technologies and Active Met...mentioning
confidence: 99%